Pengaruh Audit Internal dan Good Corporate Governance terhadap Kinerja Keuangan Perbankan - Khoirunnisah Ritonga; Mayar Afriyenti (Universitas Negeri Padang, 2023)
The aim of this study was to analyze the influence of internal audit and good corporate governance on financial performance of banking in Indonesia. The data used in this study are annual reports of banking listed on the Indonesian Stock Exchange (BEI) in the period 2018-2021. The method of taking data samples using purposive sampling method. Based on this method, a sample of 108 observations was obtained. Hypothesis testing in this study uses multiple linear regression analysis. The result show that internal audit has a negative and no significant effect on financial performance, the board of commissioners has a negative and no significant effect on financial performance, the board of directors has a negative and no significant effect on financial performance, the audit committee has a negative and no significant effect on financial performance.